The Influence of Academic Supervision and Infrastructure on Teacher Performance: Exploring the Mediating Role of Teacher Competence - Djoko Soelistya; Endale Asrat (Tinta Emas Publisher, 2024)
This research was conducted to identify factors that influence teacher performance in educational institutions, with the aim of analyzing the impact of Academic Supervision and Infrastructure on teacher performance through the medium of Teacher Competency. The type of research used is quantitative research with all school teachers as the population and 54 respondents as the sample. The research results show that Academic Supervision does not have a positive and significant influence on teacher performance, but Academic Supervision has a positive and significant influence on teacher competence. Infrastructure does not have a positive and significant influence on teacher competency and teacher performance. Meanwhile, Teacher Competency has a significant influence on teacher performance. In the context of indirect influence, Academic Supervision on teacher performance through Teacher Competency has a positive and significant influence, with Teacher Competency playing a full mediating role. On the other hand, Infrastructure on teacher performance through Teacher Competency has a positive and significant influence, but Teacher Competency acts as a partial mediation, indicating that the direct influence is more dominant. Therefore, it is necessary to improve the supervision of Academic Supervision by paying attention to teacher competency, while good infrastructure needs to be maintained to support the teacher learning process.